Higher Adherence to the Mediterranean Diet Is Associated With Preserved White Matter Integrity and Altered Structural Connectivity - Rodrigues, Belina; Coelho, Ana; Portugal-Nunes, Carlos; Magalhães, Ricardo; Moreira, Pedro Silva; Castanho, Teresa Costa; Amorim, Liliana; Marques, Paulo; Soares, José Miguel; Sousa, Nuno; Santos, Nadine Correia (Frontiers in Neuroscience, 2020)
The Mediterranean diet (MedDiet) has been associated with cognitive performance. Yet, controlled trials have yielded contradictory results. To tackle this controversy, a comprehensive multimodal analysis of the association of the MedDiet with cognitive performance and brain structure in normative aging is still necessary. To address this issue, community-dwellers ≥50 years from a cohort study on normative aging (n=76) underwent a i) magnetic resonance imaging session with two acquisitions: structural and Diffusion-Weighted Imaging; ii) neuropsychological battery of tests focusing on memory and executive functioning and iii) dietary assessment through the Mediterranean Diet Assessment Screener (MEDAS) 18 months prior to the brain imaging and neuropsychological assessment. We found that high adherence to the MedDiet (MEDAS≥10) was associated with higher values of fractional anisotropy and lower diffusivity values in the brain white matter. Similarly, high adherence to the MedDiet was associated with higher structural connectivity between left hemisphere brain regions. Specifically, the rolandic operculum, amygdala, lingual, olfactory, middle occipital gyrus, inferior occipital gyrus and calcarine areas. No association was found between high adherence to the MedDiet and total brain volumes or hypointensities. Compared to participants with low adherence to the MedDiet, those with high adherence displayed statistically significant higher memory and executive functioning scores. These results suggest that high adherence to the MedDiet positively associates with brain health, specifically with cognitive performance and white matter bundles linking regions related to the processing and integration of taste, reward and decision-making. These findings support the view that the MedDiet should be part of recommendations to promote a healthy brain.